2013
DOI: 10.3732/apps.1200515
|View full text |Cite
|
Sign up to set email alerts
|

Development of 13 microsatellite markers in the endangered Sinai primrose (Primula boveana, Primulaceae)

Abstract: • Premise of the study: We developed microsatellite markers for the endangered plant Primula boveana, the Sinai primrose, and assessed the cross-transferability of these markers to six related taxa.• Methods and Results: DNA sequences containing microsatellites were isolated from a microsatellite-enriched library. We obtained successful amplification of 13 microsatellite primer pairs, seven of which were polymorphic in P. boveana. Eleven of these primers successfully cross-amplified to related taxa.• Conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(9 reference statements)
2
5
0
Order By: Relevance
“…After several field surveys during the flowering seasons (April-July), we did not find any new population, but we confirmed five extinct localities/populations, namely Gebal Catherine (2113 m), Gebal Mousa (2285 m), Gebal Safsafa (2166 m), Gebel Umm Shaumer (2090 m), and Elgalt Elazrak (2150 m). This finding fits with the known historical distribution reported in previous literature [53][54][55][56][57][58][59][60][61]. In detail, Danin (1983) [53] indicated that P. boveana has been found in Gebal Catherine, Gebal Safsafa, and Gebel Umm Shaumer while St. Catherine rangers also reported its presence in both Gebal Catherine and Elgalt Elazrak between 2007 and 2012, but then it completely disappeared.…”
Section: The Predicted Current Suitable Sites For Survey or Translocasupporting
confidence: 92%
See 1 more Smart Citation
“…After several field surveys during the flowering seasons (April-July), we did not find any new population, but we confirmed five extinct localities/populations, namely Gebal Catherine (2113 m), Gebal Mousa (2285 m), Gebal Safsafa (2166 m), Gebel Umm Shaumer (2090 m), and Elgalt Elazrak (2150 m). This finding fits with the known historical distribution reported in previous literature [53][54][55][56][57][58][59][60][61]. In detail, Danin (1983) [53] indicated that P. boveana has been found in Gebal Catherine, Gebal Safsafa, and Gebel Umm Shaumer while St. Catherine rangers also reported its presence in both Gebal Catherine and Elgalt Elazrak between 2007 and 2012, but then it completely disappeared.…”
Section: The Predicted Current Suitable Sites For Survey or Translocasupporting
confidence: 92%
“…Moreover, increasing human disturbance on St. Catherine mountains would exacerbate the water availability problems, which affects the survival of this plant [71]. Following previous studies [57][58][59], our field observations displayed that grazing is a key pressure on P. boveana and this might explain why this species is often found on very steep cliffs. In mountainous environments, site properties vary greatly at a small scale due to differences in elevation and aspect, thus P. boveana was at a north-facing site and hence it annually receives little solar radiation.…”
Section: Future Predictive Distribution Area Of P Boveana Under Two supporting
confidence: 68%
“…The objectives were to: (i) Quantify the genetic variability and genetic structure of C. orbicularis populations; (ii) Estimate the mating systems in natural populations of C. orbicularis; (iii) Determine nuclear DNA content (ploidy). All existing populations of C. orbicularis were sampled and the genetic diversity was evaluated by simple sequence repeats (SSR) analysis utilizing a group of six novel microsatellite loci (Mansour et al, 2016), since these are considered to be appropriate for revealing genetic variation even within severely rare and endemic species (Mansour et al, 2013). Nuclear DNA content was estimated by flow cytometry; the genome size for this species is reported for the first time.…”
Section: Genetic Diversity and Inbreeding Level Ofmentioning
confidence: 99%
“…Total genomic DNA was extracted using the DNeasy Plant Mini Kit (Qiagen, Switzerland) following the manufacturer's guidelines. We amplified seven polymorphic microsatellites developed for P. boveana (Mansour et al 2013) in all the individuals sampled following the single-reaction, nested PCR method of Schuelke (2000), a cost-efficient method best suited for projects with small to moderate number of samples (Blacket et al 2012). PCRs were (Wadi Garagniah) performed in 25 lL containing 2.5 llo f1 0 9 reaction buffer, 1 ll of MgCl 2 (50 mM), 0.5 ll of a mix of all dNTPs (10 mM), 0.2 ll of the forward primer including the extended M13-tail (10 lM; Schuelke 2000), 0.5 llo f the reverse primer (10 lM), 0.5 ll of the universal M13 primer (10 lM; Schuelke 2000) labeled with a fluorophore (FAM, NED, VIC or PET), 0.1 ll of Taq DNA polymerase (Bioline; 50 U/ll), 1.0 ll of BSA (bovine serum albumin; 20 mg mL -1 ), 1.0 ll of 10 ng/lL genomic DNA, and sterilized water up to the final volume of 25 ll.…”
Section: Dna Extraction Microsatellite Amplification and Genotypingmentioning
confidence: 99%